1986
DOI: 10.1037/0022-3514.50.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strength and immediacy in group contexts: Reply to Jackson.

Abstract: This reply addresses the issues raised in Jackson's (1986) comment on Mullen's (1985a) meta-analysis of the effects of strength and immediacy in group contexts. It is reasoned that the conceptual analysis of social impact theory is unflattering but accurate, that the categorization scheme used in the metaanalysis is straightforward and defensible, and that the inclusion criteria for the meta-analysis provided the opportunity for an unbiased, stringent test of Social Impact Theory's unique treatment of strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Social Impact Theory can effectively explain the diminishing effect of increasing the number of confederates in the Asch experiments (Latane, 1981 ), and was also extended to cases where a majority conflicted with a minority (Latane and Wolf, 1981 ). However, its variables of strength and immediacy – precisely that which distinguished it from other models (e.g., Tanford and Penrod, 1984 ) – came up against conflicting empirical findings and where effects were found they were typically of a very low magnitude (Mullen, 1985 , 1986 ; Jackson, 1986 ). Furthermore, these theories were largely based on studies involving the adoption of arbitrary or bizarre group decisions and so their ability to understand social influence more generally, particularly in the context of evolution, is limited.…”
Section: The Social Psychology Literaturementioning
confidence: 97%
“…Social Impact Theory can effectively explain the diminishing effect of increasing the number of confederates in the Asch experiments (Latane, 1981 ), and was also extended to cases where a majority conflicted with a minority (Latane and Wolf, 1981 ). However, its variables of strength and immediacy – precisely that which distinguished it from other models (e.g., Tanford and Penrod, 1984 ) – came up against conflicting empirical findings and where effects were found they were typically of a very low magnitude (Mullen, 1985 , 1986 ; Jackson, 1986 ). Furthermore, these theories were largely based on studies involving the adoption of arbitrary or bizarre group decisions and so their ability to understand social influence more generally, particularly in the context of evolution, is limited.…”
Section: The Social Psychology Literaturementioning
confidence: 97%
“…In his meta-analysis, Mullen (1985Mullen ( , 1986 found that immediacy tended to exert an influence on self-report measurements of subjective anticipated tension, but not so much on other measurements that are closer to overt behavior. Although Jackson (1986) criticized Mullen's methodological approach and defended the existence of immediacy effects on overt behavior, not much support for Jackson's claims can be found in the literature until today.…”
Section: Physical Distance and Conformity To Group Normsmentioning
confidence: 99%
“…Based on metaanalyses, Mullen concluded that the effects were "weak" and "inconsistent," and hence seriously undermine the explanatory value of social impact theory. Jackson (1986) has risen in defense of the theory and has engaged Mullen in a vigorous and continuing exchange (Mullen, 1986). Whatever the direction and outcome of future research on the theory, Latane and his colleagues have thus far provided an insightful accounting of the dynamics of audience impact with the promise of a greater understanding of this topic in the future.…”
Section: Division Of Impactmentioning
confidence: 99%